Pembacaan tahlil pada aktivitas pagelaran wayang dalam tradisi Tegal Ndeso; Potret di dusun Krangrejo, Pasuruan - Mardliyatun Nahdliyah Putri; Mila Aulia; Ridya Nur Laily (STAI Darul Kamal NW Kembang Kerang, 2022)
Abstract - This study is intended to further examine the tradition of reading Tahlil in the Sandingan activity in Karangrejo Hamlet, Gempol District. The main questions to be answered are how the process of adaptation, habitualization and how the recitation of Tahlil in Wayang Performance activities can be integrated into the soul of the people of Karangrejo Hamlet? This study is a field study that is processed using a sociological approach, using the social construction theory of Peter L. Berger and Thomas Lukmann. All data in this study were obtained through observation and interviews. In this case, the data obtained from residents of Karangrejo Hamlet became primary data, while other data included secondary data. This study found that the recitation of Tahlil during Wayang Performance activities is a hereditary tradition. All series of events contain philosophical values. There are several things that have influenced external factors, namely religious leaders and others. If this is traced further based on historical data, then it is found in the tradition at the time of the Prophet. This TegalNdeso tradition was formed due to the emergence of a common taste and common opinion between individuals so that it becomes something that is inseparable or imprinted in the soul of each individual. This study found that the Koran does not only have an informative function, but the Koran also has a performative function. Thus, in practice the Koran is not only commemorated but also lived in the socio-cultural space of society.